2020
DOI: 10.1177/0954409720926016
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of the fatigue performance of elastic rail clips considering rail corrugation and dynamic axle load

Abstract: To analyze the reasons for rail clip fracture, the characteristics of rail corrugation were first measured using a rail corrugation meter. The vibration acceleration of the fastener clips at the sections with/without rail corrugation was measured, and the effects of rail corrugation on the clip vibration were analyzed. After this, a vehicle--track coupling dynamic model and a refined model for the fastener system were established in order to study the effects of rail corrugation on the vibration acceleration a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…It should be noted that the pass frequency of the 24th-order polygonal wheel at a speed of 237 km/h is close to the first-order modal frequency of the clip. Since previous studies have confirmed that resonance occurs and accelerates the clip failure when the vibration frequency excited by the wheel-rail irregularity is close to the modal frequency of the clip, 12,14,24 the effect of the resonance phenomenon on the clip failure is not discussed in this paper. In addition, comparing the clip vibration in Figure 8 with the axle box vibration in Figure 3(b), there is a significant difference for acceleration PSD.…”
Section: Effect Of 24th-order Wheel Polygonal Shape On the Vertical V...mentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the pass frequency of the 24th-order polygonal wheel at a speed of 237 km/h is close to the first-order modal frequency of the clip. Since previous studies have confirmed that resonance occurs and accelerates the clip failure when the vibration frequency excited by the wheel-rail irregularity is close to the modal frequency of the clip, 12,14,24 the effect of the resonance phenomenon on the clip failure is not discussed in this paper. In addition, comparing the clip vibration in Figure 8 with the axle box vibration in Figure 3(b), there is a significant difference for acceleration PSD.…”
Section: Effect Of 24th-order Wheel Polygonal Shape On the Vertical V...mentioning
confidence: 99%
“…On these lines, some special phenomena are found: the railway wheels are often subjected to severe polygonal wear, 23 or the rails suffer from severe corrugation. 24 High-speed trains operate at a higher speed, and the wheel-rail interaction is more violent. The fastener failure in the high-speed lines will seriously threaten the operating safety of trains.…”
Section: Introductionmentioning
confidence: 99%
“…Studies by Cui et al 2 and Hasap et al 3 have shown that under stable running conditions of railway trains, railway track components can operate, maintain, and be replaced according to design standards without premature damage. However, under typical wheel-rail coupling conditions such as rail corrugation, 4,5 uneven welding joints, 6,7 or wheel polygonal wear, 8 additional high-frequency excitation responses occur on the rail, leading to premature damage and failure of track components, particularly the clips. High-frequency vibration fatigue differs from conventional fatigue as it is closely associated with factors such as the frequency of load variations, structural resonance modes, and structural damping.…”
Section: Introductionmentioning
confidence: 99%
“…Through the wheel-rail coupling dynamics method, Ling et al (2014) verified that the static preload of clips and the cyclic wheel rail forces accelerated the fatigue damage of clips. According to the finite element method (FEM) result, Xiao et al (2017) and Wang et al (2021b) believed that the main reason for the fracture of e-shaped clips was the natural resonance fatigue caused by the rail corrugation. Hasap et al (2018) found that the life of the clips under abnormal impact load is greatly reduced, and the fracture position is consistent with the stress concentration position.…”
Section: Introductionmentioning
confidence: 99%